Analysis Determination of Firm Value: Corporate Governance Perception Index as Moderating Variable - Mardiyani, Mardiyani; Lestari, Sinta; Febriansyah, Rian; Firmansyah, Egi Arvian (Universitas Airlangga, 2024)
Background: The firm value is a crucial metric that accurately represents financial performance. Various elements influence the worth of a company inside the framework of a constantly changing worldwide market. These factors are crucial for managers, investors, and stakeholders. Establishing public trust is a crucial factor in enabling success. In 1998, Indonesia faced a monetary crisis triggered by inadequate implementation of corporate governance. Having a CGPI as a business controller enhances the comprehension of the many aspects that impact the value of a firm. Implementing GCG is an essential strategy for continually enhancing the value of a business. Objective: This research examines how the CGPI acts as a moderator, influencing the impact of profitability, dividend policy, and earnings management on firm value. Methods: This study applies a quantitative approach using purposive sampling. The object of research is companies listed on the CGPI, with data sources from the IDX and the results of the IICG assessment from 2017-2021. Methods of data analysis using Moderate Regression Analyze (MRA) with SPSS 29. Results: The research results demonstrate how businesses inform investors and lend credibility to signalling. This suggests that characteristics that influence a firm's value might be used as indicators to make decisions regarding investments. Moreover, the utilization of CGPI indicates improved financial results, suggesting efficient and clear earnings management. The CGPI effectively prevents managers from engaging in opportunistic earnings management. Conclusion: Various factors, including profitability, dividend policy, and earnings management, impact a business's value. Establishing the CGPI is essential to encouraging sustainable growth in corporate valuation. Keywords: Dividend Policy; Profitability; Earnings Management; Firm Value.